Islamic Boarding Schools Toward the Industrial Revolution 4.0; Opportunities and Challenges - Ihsan, Fanani Mafatikul; Permana, Pramudia Yuly Eka; Arifin, Nur Rachmat; Muhtadi, Ridan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
The Industrial Revolution Era 4.0 had a major impact on the life of a country. All nations are required to face this era with all the possibilities that exist. Indonesia wants to be able to compete globally, especially in the economic field. Millennial generation is considered capable of making this country more prosperous and advanced with all its characteristics, including santri. Millennial santri actually can also take part in economic growth in the Industrial Revolution 4.0 era, which is increasingly heavy competition. Through the power of MSMEs, santri and pesantren must have enormous potential in the government's big agenda, namely Indonesia 4.0. The potential for developing MSMEs can be felt more quickly if their development is supported by quality human resources and the provision of supporting facilities. Marketing training, working together with e-commerce platforms, internet procurement and supporting electronic devices, as well as network expansion to private companies and SOEs are steps that can be taken to encourage the growth of pesantren MSMEs. Through MSMEs, santri and pesantren are able to improve the country's economy but still uphold Islamic principles.